Development of MI/SD IPA Curriculum (Analysis of 2013 Curriculum Policy Formulating Patterns) - Safran, Safran (Jurnal Basicedu, 2022)
This study aims to analyze the 2013 curriculum policy for MI/SD. The focus of the study is on developing the science curriculum at the MI/SD level. This research uses a qualitative approach with a descriptive analytical study method based on library research. The use of scientific reference materials is a source of data and "tools" for data analysis of this research, which are quoted from credible pages including Google Scholar, DOAJ, Sinta, Science Direct, and Tandfonline. The results of this study indicate that the 2013 curriculum is a form of improvement from the previous curriculum related to aspects of the mindset of curriculum formulation based on the needs of students and innovative to the changes and developments of the times that are very fast. This is marked from the aspect of Graduate Competency Standards (SKL) which prioritize the needs of students, Content Standards (SI) which are integral in subjects including the formation of knowledge and skills attitudes. Furthermore, strengthening the improvement process is carried out through the use of scientific approach concepts to train students' higher order thinking skills (HOTS), as well as work process-based assessments and using student learning portfolios.